The Relationship between Adversity Quotient and Emotional Mental Disorders in Onshore Workers in The Upstream Oil and Gas Sector - Herik Okta Jonanda; Dewi Sumaryani Soemarko; Nuri Purwito Adi; Ade Mutiara; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Adversity Quotient (AQ) is an essential concept for understanding an individual’s capacity to cope with adversity, including prolonged workplace stress that may lead to Emotional Mental Disorders (EMD), particularly among Onshore workers in the upstream oil and gas sector. Harsh physical work environments and psychosocial pressures place these workers at increased risk of developing EMD. Although AQ has been shown to correlate negatively with stress, no specific research has investigated the relationship between AQ and EMD in this population. Objective: This study aims to examine the relationship between AQ and EMD among Onshore workers in the upstream oil and gas.Methods: This was an observational analytic study with a cross-sectional design involving 155 high-risk Onshore workers in the upstream oil and gas sector. Data were collected using total sampling and measured through the Self-Reported Questionnaire-20 (SRQ-20) and the Adversity Response Profile (ARP). Data analysis was conducted using the Chi-square test and Fisher’s exact test.Results: Fisher’s test results, Adversity Quotient and emotional mental disorders were not significantly related (p = 0.47).Conclusion: There is no significant correlation between Adversity quotient (AQ) and emotional mental disorders onshore workers in the upstream sector oil and gas.